TIG Welding Current Variation and Impact Strength of Aluminum Rims: Variasi Arus Pengelasan TIG dan Kekuatan Dampak Pelek Aluminium - Dimas Mahendra Wahyu Pratama; Prantasi Harmi Tjahjanti (Indonesian Journal of Innovation Studies, 2025)
General Background Welding is widely applied in construction and metal repair, requiring proper parameter selection to ensure joint quality. Specific Background TIG welding is commonly used for aluminum materials due to its precision and controlled heat input. Knowledge Gap However, limited studies focus on the relationship between welding current variation and impact strength in aluminum rims. Aims This study aims to analyze the effect of TIG welding current variations (70A, 80A, and 90A) on the impact strength of aluminum rim joints. Results The experimental results show that welding current significantly affects impact strength, with the highest value of 0.320 Joule/mm² obtained at 90A and the lowest value of 0.204 Joule/mm² at 80A. Higher current increases weld penetration and improves joint strength. Novelty This research provides specific experimental evidence on optimal current settings for aluminum rim welding using TIG. Implications The findings offer practical guidance for selecting welding parameters to achieve stronger and more reliable aluminum joints in industrial applications Keywords: Tig Welding, Aluminum Rims, Welding Current, Impact Strength, Charpy Tes Key Findings Highlights Highest toughness observed at maximum current setting Mid-level current produced the weakest joint performance Penetration depth correlates with mechanical resistance